One war, different coverage: Exploring cultural influences on international media framing of the Iraq War - Nwankpa, Nduka; Ezeji, Agnes; Chile , Solomon (American Journal of Communication, 2021)
The aim of the study was to demonstrate in empirical terms how cultural forces shape media coverage of global events. To buttress this fact, the spotlight was on international media coverage of the war in Iraq. The Iraq War was a defining media event. To underpin cultural influences on the war coverage, the paper reviewed five studies (Ravi, 2005; Dimitrova & Connolly-Ahern, 2007; Kolmer & Semetko, 2009; Barker, 2012, Gou et al., 2015) on the coverage of the war in different countries. Results revealed that the cultural context within which each news source was situated shaped the news representation of the war. The cultural factors that influenced the coverage were beyond the control of journalists and their media organizations, suggesting that culture is an important variable that should be considered when studying news production and coverage. The findings reinforce the widely held view that news production is shaped by competing influences, including cultural values.